DETERMINANTS OF HYPERTENSION IN THE ELDERLY AT SIMPANG TIGA HEALTH CENTER PEKANBARU CITY - christine vita purba; Nurhapipa .; Yuyun Priwahyuni; Rozia Daniati (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2020)
Hypertension is an increase in systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg with two measurements with calm conditions. High blood pressure or hypertension is one of the most killer diseases in the world today. According to WHO (2015) around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world was diagnosed with hypertension. The purpose of this study was to determined the determinant of the incidence of hypertension in the elderly at Simpang Tiga Health Center, Pekanbaru City in 2020. This type of research was quantitative analytic with cross sectional research design and purposive sampling technique with 183 respondents as sample from 1617 populations. The results showed that variables related to the incidence of hypertension were excessive sodium consumption with P value = 0,000, (POR = 3,874 95% CI: 2,008-7,475), physical activity P value = 0.008 (POR = 2,323 95% CI: 1,280-4,215) , and eating patterns with a value of Pvalue = 0.024 (POR = 2.302 95% CI: 1.166-4.543). It is expected that elderly program holders will provide counseling services and counseling about excessive sodium consumption and better dietary arrangements and encouraged the elderly and families to reduce foods containing excess sodium and continue to carry out physical activities, actively participating in activities held once a week at the health center/ integrated elderly development post.